Learning pathways of key occupations relevant to sustainable development in Makana Municipality - Mohanoe, Elma Nthabiseng (Rhodes University, Faculty of Education, Department of Education, 2014)
This study presents results to be contributed to the field of Environmental Education. It is a new arena for qualifications development and implementation in the South African Education and Training system. The study is located in the context of a joint research programme focusing on understanding issues of articulation and learning pathways development for sustainable development, established between the South African Qualifications Authority (SAQA) in partnership with Rhodes University, Environmental Learning Research Centre (ELRC). Phase 1 of the SAQA/ELRC research showed that researching workplace learning requires an understanding of learning pathways, if it is to be meaningful. It is for this reason that this research in phase 2 focuses specifically on learning pathways in the context of a local municipality in Makana. Using a case study research approach and qualitative data, this study investigated learning pathways for three occupational categories at different levels in the Makana Municipality: 1) key managerial occupations; 2) key supervisory occupations; and 3) key workers occupations relevant to sustainable development and how they are shaped and experienced. It also identified system and structural factors influencing articulation and access issues relevant to progress in learning pathways relevant to these key occupations. The study was designed using a case study research. Primarily, qualitative research techniques were employed to generate data, including observations, interviews and document analysis. The study used inductive, abductive and retroductive modes of inference to interpret and analyse data, using critical realist and systems perspectives. The findings on worker learning pathways show that there is a discrepancy between the Training Policy and the Environmental Training and Education Strategy of Makana Municipality. The issue of complexity in learning pathways and social structural factors such as inequality emerged as factors that strongly influenced learning pathways for workers. Learning pathways for workers involved in sustainable development practices hardly existed or simply did not exist. Interesting transitions associated with learning pathways such as from home, to work or no schooling in the case of the workers, showed a pattern of emergence. These showed that learning pathways are not accessible and equally available to everyone as can often erroneously be assumed. The findings on supervisor learning pathways show diverse complexities as well as related issues, when compared to the worker's learning pathways. Issues such as overlapping of study and work emerge as influential to supervisor learning pathways. Lack of support is, however, an influencing factor, but in a different context compared to the workers, and mainly focuses on lack of bursaries, highlighting training policy issues. This aspect was found to also relate to lack of proper resources in order to enable them to learn and do their job better; an issue raised by the workers too. This challenge of lack of support in various forms posed a barrier to learning pathways. Findings related to the manager's learning pathways show a noticeable gap between the workers, supervisors and managers. The manager's generally have higher education qualifications related to sustainable development, and in certain cases managers have had exposure to international training related to sustainable development. Factors such as ample opportunities for learning, mentoring, association on professional bodies, and decision making powers influenced the manager's learning pathways. It was also notable that while managers receive occupationally directed training, it is not necessarily sustainable development related. In theory, the results highlighted a need to understand systems as a whole and how their integration is important in influencing learning pathways. There were also underlying mechanisms and structures identified which needed to be unravelled and understood as these were found to influence learning pathways in this study. The study highlighted critical insights in understanding how learning pathways in a local municipality context (the case of Makana Municipality) are constructed by both systems and structural factors in the workplace, while also identifying ways in which agency of those engaged in learning for sustainable development in workplaces is enabled and /or constrained by such factors. It also showed the persistence of deep-seated inequalities of opportunity, especially for workers, to access and participate in sustainable development learning pathways.
Keywords: Makana Municipality; Sustainable development -- South Africa -- Grahamstown; Municipal government -- South Africa -- Grahamstown; Environmental education -- South Africa -- Grahamstown; Sustainable development -- Study and teaching -- South Africa -- Grahamstown; Vocational qualifications -- South Africa -- Grahamstown; Organizational learning -- South Africa -- Grahamstown; Educational equalization -- South Africa -- Grahamstown